A decomposed CKM model for better explaining customer satisfaction in the Jamaican public sector. (2018) - Smith, Trevor A.; Charles, Christopher A.D.
The Jamaican public sector is faced with low customer satisfaction, tight fiscal space and administrative constraints. Customer satisfaction is integral to doing business among private firms and is widely accepted as a way to sustain profits in a competitive marketplace. However, in the context of government, which is monopolistic and not market-oriented, satisfaction of customer needs is, for the most part, not focal to the business model. Notwithstanding reforms that have taken place in Jamaica's public sector, satisfaction with public service remains low and calls for an effective strategy to deliver services to customers throughout the various agencies of government. This study has addressed this gap by utilising a decomposed CKM model to better explain customer satisfaction. The results show that knowledge from, for and about the customer are associated with customer satisfaction. In the decomposed model, service, staff, advertising and promotion were positive drivers of customer satisfaction while value was a negative driver.